Pengaruh Persepsi Kegunaan, Persepsi Kemudahan, Dan Pengaruh Sosial Terhadap Minat Perilaku Wajib Pajak Orang Pribadi Dalam Menggunakan E-Filing Pada p2kp Takengon - Shella Aprillia; Reza Hanfi Lubis (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study was to determine the perceptions that influence the behavioral interest of individual taxpayers in using the e-filing system at KP2KP Takengon. This research uses quantitative descriptive. The population in this study are individual taxpayers registered at KP2KP Takengon, which opened 164,711 in 2021, spread over 1 area of ​​Takengon City. The sample in this study found 110 respondents by making a questionnaire in the form of a Google Form which was distributed to individual taxpayers who use e-filing at KP2KP Takengon. The data analysis method used in this research is multiple regression analysis and residual test for moderating variables. The results show that simultaneously, the effect of perceived usefulness, convenience and social influence of taxpayers has a significant effect on the behavioral interest of individual taxpayers in using e-filing and has a positive and significant effect on compliance in paying taxes. Then the results of the residual test show that social influence is able to improve payment performance through the e-filing system.